2020
DOI: 10.1155/2020/2408240
|View full text |Cite
|
Sign up to set email alerts
|

Selective Inhibition of PKCβ2 Restores Ischemic Postconditioning-Mediated Cardioprotection by Modulating Autophagy in Diabetic Rats

Abstract: Diabetic hearts are more susceptible to myocardial ischemia/reperfusion (I/R) injury and less sensitive to ischemic postconditioning (IPostC), but the underlying mechanisms remain unclear. PKCβ2 is preferentially overactivated in diabetic myocardium, in which autophagy status is abnormal. This study determined whether hyperglycemia-induced PKCβ2 activation resulted in autophagy abnormality and compromised IPostC cardioprotection in diabetes. We found that diabetic rats showed higher cardiac PKCβ2 activation an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 38 publications
0
2
0
Order By: Relevance
“…After development of a stable resting diameter (i.e., basal tone), the concentration-dependent vasoconstriction of coronary arterioles to PDBu was constructed and the involvements of PKC subtypes and Rho kinase were assessed with inhibitor Gö6983 (1 µmol/L) [ 79 ] against a broad-spectrum of PKC (PKCα, PKCβ, PKCγ, PKCδ and PKCζ), CGP53353 (0.3 µmol/L) against PKCβ2 [ 42 , 80 ], and Y27632 (0.1 µmol/L; Calbiochem, San Diego, CA, USA) against Rho kinase [ 20 ]. In another series of experiments, coronary arterioles were exposed to a sub-vasomotor level of PDBu (1 nmol/L) for 60 min and the vessels were challenged with the endothelium-dependent, NO-mediated vasodilators serotonin (0.1 nmol/L to 0.1 μmol/L) and adenosine (0.1 nmol/L to 10 μmol/L) and the endothelium-independent vasodilator sodium nitroprusside (0.1 nmol/L to 10 µmol/L).…”
Section: Methodsmentioning
confidence: 99%
“…After development of a stable resting diameter (i.e., basal tone), the concentration-dependent vasoconstriction of coronary arterioles to PDBu was constructed and the involvements of PKC subtypes and Rho kinase were assessed with inhibitor Gö6983 (1 µmol/L) [ 79 ] against a broad-spectrum of PKC (PKCα, PKCβ, PKCγ, PKCδ and PKCζ), CGP53353 (0.3 µmol/L) against PKCβ2 [ 42 , 80 ], and Y27632 (0.1 µmol/L; Calbiochem, San Diego, CA, USA) against Rho kinase [ 20 ]. In another series of experiments, coronary arterioles were exposed to a sub-vasomotor level of PDBu (1 nmol/L) for 60 min and the vessels were challenged with the endothelium-dependent, NO-mediated vasodilators serotonin (0.1 nmol/L to 0.1 μmol/L) and adenosine (0.1 nmol/L to 10 μmol/L) and the endothelium-independent vasodilator sodium nitroprusside (0.1 nmol/L to 10 µmol/L).…”
Section: Methodsmentioning
confidence: 99%
“…A recent study suggested that autophagy is necessary to decrease myocardial damage following acute myocardial ischemia and that autophagy limits activation of the NLR family pyrin domain-containing 3 (NLRP3) inflammasome by removing damaged mitochondria ( 43 ). However, it is also reported that excessive autophagy during reperfusion may aggravate the injury of the heart ( 107 , 108 ).…”
Section: Pathophysiological Mechanisms Of Mirimentioning
confidence: 99%